Analisis Produktivitas Produksi Roti Manis PT. Indoroti Prima Cemerlang (Mr.Bread) Badung - Prascita, Putu Shangrila Revia Parameswari; Satriawan, I Ketut; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
Indoroti Prima Cemerlang Corporate, also known as Mr. Bread, is one of the companies produces various kind of bread. In producing bread, the company always optimizes the usage all available sources. Analyzing productivity rate could be done by measuring the productivity of the production division. On the productivity rate measurement process Indoroti Prima Cemerlang Corporate was using objective matrix method (OMAX) and six ratios. Four ratios were the assessment of efficiency criteria, one ratio was used to assess inferential criteria, and the last one ratio was used for effectivity criteria. The highest productivity rate of sweet bread was achieved on June 2020, which increased up to 2,8% with productivity index 292,6. On contrary, the lowest productivity rate was 22,5% on April 2020, with productivity index 215,8. The linkage analysis of each productivity ratio component process to sweet loaf production in Indoroti Prima Cemerlang Corporate result was on ratio 6 with value 212,5, and ratio 2 with value 319,6. In order to improve the productivity, it is recommended to modify the ratio 1 into 190 hours, ratio 2 into 43.810.023 IDR, ratio 3 into 294.291.081 IDR, ratio 4 into 55 people, ratio 6 into 3.006.399.330 IDR and ratio 6 into 184 hours. Keywords : productivity, production, Objective Matrix (OMAX)